2015
DOI: 10.22146/gamaijb.8504
|View full text |Cite
|
Sign up to set email alerts
|

Socioemotional Wealth and Firms’ Control: Evidence from Malaysian Chinese Owned Companies

Abstract: This paper explores how the preservation of socioemotional wealth can be manifested in the control and corporate governance of Malaysian Chinese firms. Using panel data from the Industrial Products index of the Bursa Malaysia (the Malaysian stock exchange) during 2003-2006, we show that the ingrained 'life-raft values' among overseas Chinese entrepreneurs can be associated with the preservation of their socioemotional wealth, and thus they prioritize control over their firms. Additionally, we confirm the monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
0
6
0
2
Order By: Relevance
“…The main characteristic of a family firm is the presence and performance of its founder. Some authors maintain that institutions with family firm characteristics, such as the concentration of ownership and management in a single family, also impact on their respective levels of performance (Chien, 2014; Goh et al , 2015; Kota and Singh, 2016). Family companies are those founded and handed down from generation to generation within the scope of the same family, whether or not managed by members of the family with or without assistance from professional managers (Goh et al , 2015; Kota and Singh, 2016; Mokhber et al , 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristic of a family firm is the presence and performance of its founder. Some authors maintain that institutions with family firm characteristics, such as the concentration of ownership and management in a single family, also impact on their respective levels of performance (Chien, 2014; Goh et al , 2015; Kota and Singh, 2016). Family companies are those founded and handed down from generation to generation within the scope of the same family, whether or not managed by members of the family with or without assistance from professional managers (Goh et al , 2015; Kota and Singh, 2016; Mokhber et al , 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some authors maintain that institutions with family firm characteristics, such as the concentration of ownership and management in a single family, also impact on their respective levels of performance (Chien, 2014; Goh et al , 2015; Kota and Singh, 2016). Family companies are those founded and handed down from generation to generation within the scope of the same family, whether or not managed by members of the family with or without assistance from professional managers (Goh et al , 2015; Kota and Singh, 2016; Mokhber et al , 2017). Within this same line of thinking, even those that do not participate in companies of this nature may imagine how involving persons from the same family may hinder every type of decision and negotiation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…2.2.4 Non-debt tax shields. Non-debt tax shields have been used indirectly to shrink firms' long-term debt ratios and lowering the costs of issuing debt (Nhung et al, 2017;Goh et al, 2018) while Kanatani and Yaghoubi (2017) found that non-debt tax shields positively impact leverage ratios. Dan et al (2015), however, found this connection to be insignificant for private firms.…”
Section: Corporate Tax In Malaysiamentioning
confidence: 99%
“…Penelitian terdahulu yang dilakukan oleh Dewi & Sudiartha (2017), Puspita & Dewi (2019), Apsari & Dana (2018), Mujiatun et al (2021), dan menunjukkan bahwa profitabilitas berpengaruh positif pada struktur modal. Hasil yang berbeda ditemukan pada penelitian yang dilakukan oleh Mota & Moreira (2017), Ngjeliu (2018), Kythreotis et al (2017), Goh et al (2018), dan Khafid et al (2020) yang menunjukkan hasil bahwa profitabilitas berpengaruh negatif pada struktur modal.…”
Section: Gambar 1 Debt To Equity Ratio Perusahaan Nonkeuangan Yang Te...unclassified